1996
DOI: 10.1103/physrevc.54.1427
|View full text |Cite
|
Sign up to set email alerts
|

Modified quark-meson coupling model for nuclear matter

Abstract: The quark-meson coupling model for nuclear matter, which describes nuclear matter as non-overlapping MIT bags bound by the self-consistent exchange of scalar and vector mesons, is modified by introducing medium modification of the bag constant. We model the density dependence of the bag constant in two different ways: one invokes a direct coupling of the bag constant to the scalar meson field, and the other relates the bag constant to the in-medium nucleon mass. Both models feature a decreasing bag constant wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
154
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(160 citation statements)
references
References 73 publications
4
154
2
Order By: Relevance
“…B/B 0 ∼ 35 − 40% at the nuclear matter saturation density, the predictions for the rescaling parameter are in good agreement with those required to explain the depletion of the structure function observed in a range of nuclei. Such a large reduction of the bag constant, as shown in previous works [11,12], also implies large and canceling Lorentz scalar and vector potentials for the nucleon in nuclear matter which are comparable to those suggested by the relativistic nuclear phenomenology and finite-density QCD sum rules. This indicates that the reduction of bag constant and hence the increase of confinement size in nuclei may play important role in low-and medium-energy nuclear physics and the modified QMC model provides a useful framework to accommodate both the change of confinement size and the quark structure of the nucleon in describing nuclear phenomena.…”
Section: Introductionsupporting
confidence: 72%
See 2 more Smart Citations
“…B/B 0 ∼ 35 − 40% at the nuclear matter saturation density, the predictions for the rescaling parameter are in good agreement with those required to explain the depletion of the structure function observed in a range of nuclei. Such a large reduction of the bag constant, as shown in previous works [11,12], also implies large and canceling Lorentz scalar and vector potentials for the nucleon in nuclear matter which are comparable to those suggested by the relativistic nuclear phenomenology and finite-density QCD sum rules. This indicates that the reduction of bag constant and hence the increase of confinement size in nuclei may play important role in low-and medium-energy nuclear physics and the modified QMC model provides a useful framework to accommodate both the change of confinement size and the quark structure of the nucleon in describing nuclear phenomena.…”
Section: Introductionsupporting
confidence: 72%
“…The reader is referred to Refs. [11][12][13] for further details and motivations for introducing the medium modification of the bag constant.…”
Section: The Modified Qmc Model and Bag Radius In Nucleimentioning
confidence: 99%
See 1 more Smart Citation
“…We obtained the nucleon wave function from the Faddeev equation and showed that the nucleon size significantly increases in the medium. This implies a swollen nucleon in nuclear matter which has many attendant consequences [38,39,40,41]. Our estimation of in-medium nucleon size should be taken more qualitatively since the quark density function given in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…The model has been further developed by several authors [17][18][19][20][21]. An important revision of the model was made in Ref.…”
Section: Introductionmentioning
confidence: 99%